O eu e o tu no discurso da publicidade agrícola : uma relação efetiva? - Borges, Juliane (2015)
This study entitled The I and You in the speech of the agriculture s advertisement: An effective relation? intents to analyse the relation between the I and the You in the advertisement directed to the agriculture segment, using as reference the theory of Émile Benveniste. The study begins from the purpose of verifying the effectivity of the relation between the advertising companies (I) and the consumers in the agriculture segment (You), by means of the analysis of the appropriation of the language system by the advertisement and the establishment of the relation between the I and the You in the publicitary speech, as well as the recognizement of the You (product/brand) by the target-public (farmers).To fulfill the objectives of the study, it was used as a base the Enunciation Theory of Émile Benveniste presented in the texts: The Nature of the Pronouns (1956); Of the Subjectivity in the Language (1958); Semiology of the Language (1969) and The Formal Device of the Enunciation (1970). The corpora of the research are constituted by speech of sixteen farmers interviewed, of which four integrated the analysis, and five printed media advertisements. The research is qualitative, developed with base in field study, and the data collection technique was the in terview in depth, with semi-open questions. The analysis, done after segments of the transcription of the interviews, had as selection criteria the most complete answers. The analysis of the segments of the interviews sought evidence of the identification of the farmers as the You of the publicitary speech, of the compreension of the publicitary message present in the advertisements and of the recognizement of the It (product/announced brand), by means of the appropriation of the categories of enunciation (person, time and place) and its relation with three guidelines of the publicitary production: a) knowledge about the target-public (social, cultural and economic profile); b) knowledge about the buying-behavior of the target-public (needs, influences, references and preferences); c) knowledge about the segment of acting of the advertiser (agriculture market). The results indicate that there is, in fact, difficulty in the compreension by the farmers of the content of the publicitary message, as they do not identify themselves, and thus not establishing na effective relation between the I and the You. The most evident factor in the farmers speech is the absence of the identification of the It (product/announced brand), since that, as subject of the enunciation, when putting themselves as the I to analyse the advertisements, the interviewed do not put the non-person in their speech, and that invalidate its presence in the interaction advertiser-consumer